A Multidisciplinary Approach To Sport Tourism Education In A Digital Era - Vrondou, Ourania; Katsoni, Vicky C (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2017)
Sport tourism has enjoyed a plethora of definitional and theoretical perspectives over the last three decades proposing a dynamic alternative to mass tourism with specific structural features and modus operandi. However, studies examining or suggesting the basic body of knowledge that would satisfy the educational needs of participants in this complex tourism form are lacking. The present study aims to minor the gap of theoretical support and direction for tourism academics and sport and tourism managers through an analysis of the involved conceptual fields. Hopefully, the result will offer a vision on the further development of sport tourism education to meet the needs of one of the most promising leisure forms. Following an analysis of the major challenges sport tourism education is facing, the article proposes the basic dimensions of a conceptual framework on which to base development of a sport tourism management curriculum.